The degree of business organizations’ activity in the areas of social responsibility in the Sultanate of Oman during 2020-2021 from the point of view of society in the governorates (Al Dakhiliyah, Al Batinah and Al Wusta) - AL-Hadhrami, Ahmed Saeed Nasser; Al-Saeedi, Hamid Muslim; Alhadhrami, Nail Sulaiman (Journal of Humanities & Social Sciences, 2022)
The study aimed to identify the degree to which business organizations practice the areas of social responsibility in the Sultanate of Oman from the point of view of community members in the governorates (Al Dakhiliyah, Al Batinah and Al Wusta governorates as a model), and used the descriptive analytical approach, and used the questionnaire as a tool, and was applied to a sample of (150) community members in the governorates (Al Dakhiliyah, Al Wusta, Al Batinah) The results of the study showed the following: The degree of practice and contribution of business organizations to the local community in the fields (economic, social, environmental, health, education and scientific research) came at a very low and weak level, and the order of business organizations’ practice of the areas of social responsibility according to the role played by business organizations from the point of view of community members in the Sultanate of Oman came. In the following order (the environmental field - the health field - the social field - the field of education and scientific research - the economic field) and the study indicated that there are no statistically significant differences in the practice of business organizations in the areas of social responsibility due to the location of the organizations in the governorates Based on the research of the study, the researchers recommend that the government adopt strict laws and procedures that it imposes on business organizations in local communities regarding the practice of areas of social responsibility, through the establishment of a supervisory body for this issue.